Biomolecule‐Assisted Synthesis of Hierarchical Multilayered Boehmite and Alumina Nanosheets for Enhanced Molybdenum Adsorption. Issue 18 (5th March 2019) - Saptiama, Indra; Kaneti, Yusuf Valentino; Yuliarto, Brian; Kumada, Hiroaki; Tsuchiya, Kunihiko; Fujita, Yoshitaka; Malgras, Victor; Fukumitsu, Nobuyoshi; Sakae, Takeji; Hatano, Kentaro; Ariga, Katsuhiko; Sugahara, Yoshiyuki; et al.
Abstract: The effective utilization of various biomolecules for creating a series of mesoporous boehmite (γ‐AlOOH) and gamma‐alumina (γ‐Al2 O3 ) nanosheets with unique hierarchical multilayered structures is demonstrated. The nature and concentration of the biomolecules strongly influence the degree of the crystallinity, the morphology, and the textural properties of the resulting γ‐AlOOH and γ‐Al2 O3 nanosheets, allowing for easy tuning. The hierarchical γ‐AlOOH and γ‐Al2 O3 multilayered nanosheets synthesized by using biomolecules exhibit enhanced crystallinity, improved particle separation, and well‐defined multilayered structures compared to those obtained without biomolecules. More impressively, these γ‐AlOOH and γ‐Al2 O3 nanosheets possess high surface areas up to 425 and 371 m 2 g −1, respectively, due to their mesoporous nature and hierarchical multilayered structure. When employed for molybdenum adsorption toward medical radioisotope production, the hierarchical γ‐Al2 O3 multilayered nanosheets exhibit Mo adsorption capacities of 33.1–40.8 mg g −1 . The Mo adsorption performance of these materials is influenced by the synergistic combination of the crystallinity, the surface area, and the pore volume. It is expected that the proposed biomolecule‐assisted strategy may be expanded for the creation of other 3D mesoporous oxides in the future. Abstract : Biomolecular influencer : Mesoporous γ‐Al2 O3 nanosheets with unique hierarchical multilayered structures have been fabricated in the presence of biomolecules (see figure). They exhibit high molybdenum adsorption capacities up to 40.8 mg g −1 .